Synthesis, Mechanistic and Kinetic Study of 2,4,5-Trichloroaniline Phosphate Monoester - Tiwari, B.K.; Agarwal, Anupam; Singh Parihar, Pushpraj; Kumar Dixit, Vikas; Kadam, Rishika; Singh, Rajesh; Singh, Peetam; Gupta, C.P. (Asian Journal of Chemistry, 2010)
Kinetic measurement of the hydrolysis of 2,4,5-trichloroaniline phosphate mono-ester has been made in acid (0.1-6.0 mol dm3 HCl) solution at 97 ± 0.5ºC supported the hypothesis that acid catalysis occurs only when electron attracting substituent is present in the aryl part. Pseudo first order rate coefficients have been calculated. Conjugate acid, neutral and mononegative species have been found to be reactive and contribute in the overall rates. The rate coefficients estimated are fairly in good agreement with the observed rates. Bond fission, molecularity and order of reaction have been supported by Arrhenius parameters, Zucker- Hammett hypothesis, concentration and solvent effect etc. Comparative isokinetic rate data of similarly substituted other amino phosphate mono-esters, supported P–N bond fission.